2019
DOI: 10.34257/gjmbravol19is3pg1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Conflict Management Styles on Team Performance on Supervisors of Teams in Universities

Abstract: This study investigates the impact of conflict management (CM) styles on team performance. Conflict Management was conceptualized in terms of five styles: avoiding, integrating, dominating, obliging and compromising. Team performance, on the other hand, was operationalized in terms of team cohesion, team communication, innovativeness, and quality. Five hypotheses regarding the impact of each dimension of CM on team performance were postulated. Gathering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…Unlike the use of integrating and compromising which bring together the concerns for both parties, the use of dominating and obliging only focuses on one of the involved parties (e.g., only concern for self: dominating, only concern for others: obliging), whereas avoiding is preferred when the employee simply wants to withdraw from the conflict situation. As a result, these three maladaptive strategies (dominating, obliging, and avoiding) are often associated with negative outcomes, such as amplified strain ( Dijkstra et al, 2009 ) or lowered team performance ( Alhamali, 2019 ), thus a similar result pattern was observed among these three strategies in the present study.…”
Section: Results and Discussion Of Studysupporting
confidence: 80%
See 2 more Smart Citations
“…Unlike the use of integrating and compromising which bring together the concerns for both parties, the use of dominating and obliging only focuses on one of the involved parties (e.g., only concern for self: dominating, only concern for others: obliging), whereas avoiding is preferred when the employee simply wants to withdraw from the conflict situation. As a result, these three maladaptive strategies (dominating, obliging, and avoiding) are often associated with negative outcomes, such as amplified strain ( Dijkstra et al, 2009 ) or lowered team performance ( Alhamali, 2019 ), thus a similar result pattern was observed among these three strategies in the present study.…”
Section: Results and Discussion Of Studysupporting
confidence: 80%
“…Limitation = Focus on limitations. * p < 0.05; * * p < 0.01; * * * p < 0.001; + p = 0.051. maladaptive strategies (dominating, obliging, and avoiding) are often associated with negative outcomes, such as amplified strain (Dijkstra et al, 2009) or lowered team performance (Alhamali, 2019), thus a similar result pattern was observed among these three strategies in the present study.…”
Section: Indirect Effect Of Age On Conflict Management Strategies Thrsupporting
confidence: 85%
See 1 more Smart Citation
“…Under cooperative styles, the diversity of views gets harnessed, and “premature closure of debate over policy alternatives” can be avoided, resulting in better decisions (Coggburn et al, 2014, p. 508; Wang et al, 2020). It has been argued that through encouraging team members to explore multiple alternatives and integrating opposing positions through logical argumentation and explanation, cooperative conflict management style results in better solutions and decisions and, subsequently, better team performance (Alhamali, 2019; Behfar et al, 2008; DeChurch et al, 2013; Tjosvold et al, 2014; Yin et al, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Finally, by passively ignoring disagreements, avoidant forms of conflict management tend to harm group performance (Alhamali, 2019; Tjosvold et al, 2014). Behfar et al (2008) found that teams with consistently low or decreasing performance, experienced avoidant forms of conflict management, by simply giving in consensus instead of engaging in debate.…”
Section: Theoretical Frameworkmentioning
confidence: 99%